2018
DOI: 10.1002/jctb.5809
|View full text |Cite
|
Sign up to set email alerts
|

Association of robust nitrogen removal with spatiotemporal nitrifying bacterial community dynamics in a new bioreactor for treatment of simulated livestock wastewater with high ammonia content

Abstract: BACKGROUND Different types of nitrogen‐containing wastewater have been treated with dewatered alum sludge (DAS) or neutralized used acid (NUA) or with a combined DAS–NUA biofilter. The connections between the spatiotemporal structures of ammonia‐oxidizing bacteria (AOB) and nitrite‐oxidizing bacteria (NOB) and the nitrogen removal performance of DAS–NUA biofilter have not been fully clarified. To address this issue, AOB and NOB genetic characteristics response to nitrogen conversions in a laboratory‐scale DAS–… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 38 publications
2
5
0
Order By: Relevance
“…As shown in Figure 6C, the relative abundance of Nitrobacter in each sample was the highest (from 86.95 to 99.99%). This is consistent with the previous study, which has described that Nitrobacter is the single abundant genus in NOB (Zhang et al, 2019). However, it is opposite to another study using laboratory-scale devices, which has reported that Nitrospira is the predominant genus in NOB (Sayess et al, 2013).…”
Section: Comparative Analysis Of Microbial Community Structuresupporting
confidence: 91%
See 4 more Smart Citations
“…As shown in Figure 6C, the relative abundance of Nitrobacter in each sample was the highest (from 86.95 to 99.99%). This is consistent with the previous study, which has described that Nitrobacter is the single abundant genus in NOB (Zhang et al, 2019). However, it is opposite to another study using laboratory-scale devices, which has reported that Nitrospira is the predominant genus in NOB (Sayess et al, 2013).…”
Section: Comparative Analysis Of Microbial Community Structuresupporting
confidence: 91%
“…The correlation between the genus and nitrogen removal ( Table 4) further indicated that NH 4 + -N concentration was significantly negatively correlated with Candidatus Nitrosotenuis (belongs AOA), Nitrobacter (belongs NOB), and Planctomyces (belongs to V4−V5 region microorganisms) with R-values of −0.617 (P < 0.05), −0.648 (P < 0.01), and −0.819 (P < 0.01), respectively. Candidatus Nitrosotenuis was the dominant genus of AOA, and a low C/N ratio could significantly promote its relative abundance in the cathode layer during the stabilization period; thus, this genus is more conducive to the conversion of NH 4 + -N. Furthermore, as the most abundant genus of NOB, Nitrobacter is suitable for NH 4 + -N removal in wastewater, which has also been confirmed by our previous study (Zhang et al, 2019).…”
Section: Pearson Correlation Between Microbial Characteristic Parametsupporting
confidence: 80%
See 3 more Smart Citations